Structural and functional analyses of Pr-induced variants of XccBphP bacteriophytochrome from Xanthomas campestris - Conforte, Valeria Paola (2021)
Photoreceptors are able to detect light and transduce that signal generating a cellular response. Among them are the red/far red light sensing bacteriophytochromes (BphP). These bilin-binding proteins have the ability to photoswitch between two states, a red-absorbing (Pr) and a far-red-absorbing (Pfr), by the isomerization of the bilin chromophore and generating structural changes that result in the transduction of the light signal into biochemical signaling. The genome of Xanthomonas campestris pv. campestris (Xcc), the causative agent of black rot in crucifers, codes for a functional BphP (XccBphP) which was extensively described in previous studies. It has been defined as a negative regulator of several light-mediated mechanisms involved in its virulence. Here, we deepened the analysis of the XccBphP structure and function. In this work, we designed and constructed three different variants with single amino acid changes that affect XccBphP photocycle favoring its Pr state: L193Q, L193N and D199A. We purified the recombinants full-length mutants, crystalized them and solved their crystal structures, showing a Pr conformation almost identical to the wild-type previously obtained. We also examined their UV-Vis absorption spectroscopic properties, proving that Pr is their preferred state. After establishing the effect of each mutation on the structure of XccBphP, we tested the effects of altering the XccBphP photocycle using exopolysaccharide (EPS) production and stomatal aperture assays as indicators of its bacterial signaling pathway. Null mutant complementation assays showed that L193Q or L193N Pr-stabilized versions decreased bacterial EPS production in darkness or under far-red light and increased it under red light in an amplified manner compared to the complementation with the wild-type version. Furthermore, strains expressing Pr-favored XccBphP versions could not promote stomatal reopening at Xcc null mutant levels when tested in Arabidopsis epidermis. Taken together, our results highlight the relevance of the XccBphP Pr-Pfr balance in physiological processes in Xcc.